If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 34 + -6x = 124 Solving 34 + -6x = 124 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-34' to each side of the equation. 34 + -34 + -6x = 124 + -34 Combine like terms: 34 + -34 = 0 0 + -6x = 124 + -34 -6x = 124 + -34 Combine like terms: 124 + -34 = 90 -6x = 90 Divide each side by '-6'. x = -15 Simplifying x = -15
| 4(450-b)=75 | | -12=3(x-4)-3x | | 4y^2-[-3y-(19y^2-4y)]-[5+(-9y-5)]= | | 5-4x-6=7 | | 29-3x=-13 | | 4(75-b)=450 | | 9+2x-17=144 | | 25+3x=61 | | -10=-14v+14x | | log(16)*8=x | | 4(450-75)=b | | 7y^2-[-5y-(4y^2-8y)]-[2+(17y-2)]= | | 4=t/11 | | 9x+3x-10=3(3x-2x) | | V/9=2 | | 0.5x-x=-2 | | D=1/14w2-5/7w= | | 0.5x-x=2 | | b^2-8b+16=12 | | X^2-1/3x-2/3=0 | | -8x^2-[8x-(6x^2-8x)]-[7+(-8x-7)]= | | 40=8x+4 | | x(1/5)=60 | | -21+11a=111 | | 8t+16=209 | | 4e^3-8=-6 | | M^2-m+7=0 | | 2(x-6)(2x+3)=0 | | 7j+3r+9= | | (-5)*x-(1)=44 | | 7(9*7)/4 | | 7x^2-48x-34=0 |